Pengaruh Kompensasi, Punishment dan Keselamatan Kerja terhadap Kinerja Karyawan di PT XYZ - Vikry Agung Prasetiyo; Heru Baskoro (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study aims to further understand the influence of compensation, punishment, and occupational safety on employee performance at PT. XYZ. Compensation is seen as an important element that can motivate employees to increase work productivity, while punishment or appropriate and fair punishment serves as a tool to control behavior to comply with company rules and standards. In addition, occupational safety is also a crucial factor because a safe work environment will encourage employees to work more calmly, comfortably, and optimally. The research method used is a quantitative approach with data collection techniques through questionnaires distributed to a number of PT. XYZ employee respondents. The collected data were then analyzed using multiple linear regression to determine the magnitude of the influence of the independent variables on the dependent variable, namely employee performance. The results of the study indicate that compensation has a positive and significant effect on employee performance. Providing appropriate compensation that is in accordance with employee contributions can increase work motivation and encourage the achievement of company targets. Furthermore, punishment also has a significant effect, where a punishment system that is applied consistently, fairly, and transparently has been proven to reduce the level of disciplinary violations and increase employee responsibility. Occupational safety factors have also been shown to have a significant influence on performance, as a safe and healthy work environment provides a sense of comfort and reduces the risk of workplace accidents that can decrease productivity. Based on the results of this study, it can be concluded that compensation, punishment, and occupational safety simultaneously or partially contribute significantly to improving the performance of PT. XYZ employees.